Genetic Polymorphisms of the Vitamin D Receptor ApaI Gene and Physiological Parameters Diversity of Polycystic Ovary Syndrome in Iraqi Women - Safa F. Ali; Shiva Khezri; Ilham A. Khalaf; Dalia J. Mahmood (Iraqi Journal of Industrial Research)
Polycystic ovary syndrome (PCOS) is a prevalent hormonal disorder among women of reproductive age, requiring diverse management strategies. This study, conducted at Kamal Al-Samarrai Hospital Fertility Center/Baghdad from January to March 2023, included 80 Iraqi women aged 18-45, comprising 40 with PCOS and 40 healthy controls. Hormonal markers (FSH, LH, T, PRL, Ca2+, and Vitamin D3) were systematically assessed, along with Apa1 gene polymorphisms in whole blood genomic DNA using PCR-RFLP. PCOS patients showed significantly elevated LH, LH/FSH, T, and PRL levels (p < 0.01) and lower Vitamin D and calcium levels (p < 0.05) compared to controls. The scrutiny of VDR gene Apa1 polymorphism uncovered a notable prevalence of "Aa" and "aa" genotypes among PCOS patients, constituting 65.00% and 25.00%, respectively, in contrast to the control group's 17.50% and 0.00% in controls. The "aa" allele, more frequent in PCOS, emerged as a potential risk factor for the condition. This study establishes a strong association between VDR gene (Apa1) polymorphism and PCOS, highlighting the significance of the "aa" allele. It emphasizes the homozygous variant genotype "aa" as a substantial risk factor for PCOS, providing insights into its genetic basis.